Estimates of length-based population parameters of the skipjack tuna, Katsuwonus pelamis (Linnaeus, 1758) in the Andaman waters - Pradeep, H.D.; Shirke, Swapnil Shivdas; Kar, Annada Bhusan (Journal of Fisheries, 2017)
The exploitation of Katsuwonus pelamis in Andaman waters is meagre compared to its total landings in India. As the population parameters of this species has not been attempted in these waters, an attempt has been made here to estimate the population parameters of K. pelamis based on the length frequency data collected from local fishing boats operating from Junglighat Fishing Harbour, Port Blair, Andaman Islands from January to December 2014. A total of 704 specimens ranging from 16.5 to 71.0 cm fork length were taken for analysis. The parameters L∞, K and t0 were 74.55 cm, 0.59/year and –0.21 respectively. The von Bertalanffy growth equation for K. pelamis is Lt = 74.6[1 – e–0.59(t+0.214255)]. The recruitment pattern was unimodal. The recruitment period was from July – October. The longevity of the species was calculated as 4.9 years. After 1st, 2nd, 3rd and 4th year the length attained by the species is 38.1, 54.4, 63.4 and 68.3 cm respectively. The mortality parameters were Z=2.07, M=0.93, F=1.14 and exploitation ratio was 0.55. The virtual population analysis for K. pelamis indicated that fishing mortality starts at 41–50 cm class interval and it continues henceforth and was maximum at 61–70 cm and decreased thereafter.